2000
DOI: 10.1210/mend.14.7.0493
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 Binding Sites and An Estrogen Response Element Half-Site Are Involved in Regulation of the Human Progesterone Receptor A Promoter

Abstract: Progesterone receptor gene expression is induced by estrogen in MCF-7 human breast cancer cells. Although it is generally thought that estrogen responsiveness is mediated through estrogen response elements (EREs), the progesterone receptor gene lacks an identifiable ERE. The progesterone receptor A promoter does, however, contain a half-ERE/Sp1 binding site comprised of an ERE half-site upstream of two Sp1 binding sites. We have used in vivo deoxyribonuclease I (DNase I) footprinting to demonstrate that the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
95
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 59 publications
9
95
0
Order By: Relevance
“…It has been demonstrated that this half-ERE/Sp1 binding site is protected to a greater extent when MCF-7 cells are treated with estrogen, suggesting that this region may be involved in estrogen-regulated gene expression. 28) These results also suggest that, in human breast cancer, PRA may be more closely regulated by estrogen through ERα than PRB. Both PRA and B promoters have been reported to be regulated by estrogen, but there may be different pathways, or responsiveness to estrogen actions.…”
Section: Discussionmentioning
confidence: 69%
“…It has been demonstrated that this half-ERE/Sp1 binding site is protected to a greater extent when MCF-7 cells are treated with estrogen, suggesting that this region may be involved in estrogen-regulated gene expression. 28) These results also suggest that, in human breast cancer, PRA may be more closely regulated by estrogen through ERα than PRB. Both PRA and B promoters have been reported to be regulated by estrogen, but there may be different pathways, or responsiveness to estrogen actions.…”
Section: Discussionmentioning
confidence: 69%
“…This receptor is one of the most intensely studied estrogen-regulated genes and is widely recognized as a marker of estrogen activity [32]. Clusters of estrogen response element (ERE) half-sites, which are essential for transactivation of the PR gene by liganded response elements, are present within the PR gene promoter [33][34][35]. Almost all hormone treatment protocols designed to elicit effects of progesterone involve preparatory estrogen priming to induce PR [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these experiments used reporter constructs containing a consensus oestrogen response element (ERE) from the vitellogenin gene to examine the effects of the BRCA1 protein on ERa transcriptional activity (Fan et al, 1999), whereas others have shown that overexpression of BRCA1 abrogates the effects of E 2 on expression of the oestrogen-induced genes, pS2 and cathepsin D (Fan et al, 2001). The PgR gene promoter does not contain a complete ERE but it does have ERE half sites adjacent to those for Sp-1 (Petz and Nardulli, 2000), and it is possible that the BRCA1 protein has significantly different effects at this site in human breast epithelium in vivo. Alternatively, the differences in expression of PgR in response to E 2 treatment may result from an alteration in the ratio of the A and B isoforms of the PR.…”
Section: Discussionmentioning
confidence: 99%